PENGARUH PERKEMBANGAN SEKTOR KEUANGAN TERHADAP KUALITAS LINGKUNGAN DI NEGARA ANGGOTA OKI TAHUN 2003-2017 - Wafdah Layli Rizqiyah; Ilmiawan Aumalim (Universitas Islam Negeri Sumatera Utara, 2022)
This study identifies the effect of the development of the financial sector on environmental quality. The proxy of the environmental Quality indicator is CO2 emissions, while financial sector development is explained by 4 variables. This study uses STATA 13 application and panel data regression analysis techniques. The results showed that there was a significant influence between the ratio of liquidity liabilities to GDP, the ratio of domestic credit to the private sector to GDP, the ratio of stock market capitalization to GDP, stock market turnover ratio, and simultaneous economic growth on the environment of degradation. Meanwhile, each has a different variation. Turnover Stock market ratios and economic growth do not significantly affect environmental quality in OIC Member Countries. The limitation of this study is the number of sample countries only 8 out of 57 OIC Countries, because of the limited data available.